ANALISA PENGARUH BEBAN PENGEREMAN DAN VARIASI MERK KAMPAS REM TERHADAP KEAUSAN KAMPAS REM - Ismet Eka Putra; Jecky Agusti (Rang Teknik Journal, 2020)
The level of use of motor vehicles is increasing every year and will cause a high need for brake canvas. So we need a brake canvas that has a level of wear as small as the original canvas. Many brake canvas manufacturers introduce brake canvas with different brands such as the C and W brands, the brand is no less good quality with Original. The purpose of this test is to find out how much the difference in wear value between the original Y brake canvas with the C and W brands when load variations are given. So get a wear value with the Y original brand: the first test with a load of 1.5 kg and a wear value of 2.82 gr/mm2.second, in the second test with a load of 2 kg and a wear value of 6.07 gr/mm2.second, in the third test with a load of 2.5 kg and a value of 6.32 gr/mm2 second wear. With the C brand: the first test with a load of 1.5 kg and a wear value of 5.99 gr/mm2.second, in the second test with a load of 2 kg and a wear value of 3.74 gr/mm2.second, in the third test with a load of 2,5 kg and wear value 7.51 gr/mm2.second. With the W brand: the first test with a load of 1.5 kg and a wear value of 3.76 gr/mm2.second, in the second test with a load of 2 kg and a wear value of 5.28 gr/mm2.second, in the third test with a load of 2,5 kg and a wear value of 6.98 gr/mm2 seconds. So, from the results of tests conducted can be the wear values of each brake canvas and with the existing graphs show that the brake canvas of the C and W brands are also no less good quality with the Y Original brand.